Strategi Guru Pai Dalam Pembentukan Akhlaq Pada Siswa Guna Meningkatkan Prestasi Ubudiyah Di SMK An Nur Al Muntahy - Ach. Romli (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
SMK An-Nur Al Muntahy is a vocational high school (SMK) located within the environment of an Islamic boarding school (pondok pesantren). This means that the school provides technological education with a pesantren background. The religious routines practiced at SMK An-Nur Al Muntahy can serve as a model for general schools in fostering intellectually capable generations with noble character. This study aims to determine: 1) The strategies for shaping students' character to improve ubudiyah performance in Class XI TKJ 1 at SMK An-Nur Al Muntahy, Kembang Jeruk, Banyuates, Sampang. 2) The supporting and inhibiting factors of these strategies in shaping students' character to improve ubudiyah performance in the same class. This research uses a qualitative approach. Data were collected through interviews, observations, and documentation. The data obtained in the field were then organized by selecting and simplifying the information. Afterward, the data were presented to draw conclusions. The results of the study indicate that: (1) Strategies for shaping students’ character to improve ubudiyah performance in Class XI TKJ 1 at SMK An-Nur Al Muntahy include: personal approach, instilling good habits, providing exemplary behavior, and conveying moral lessons (hikmah). (2) The supporting and inhibiting factors in the implementation of these strategies are as follows: a. Supporting factors: motivation, parental support, and shared commitment. b. Inhibiting factors: lack of awareness and negative influences from the surrounding community (peer interaction).